COVID-19 associated mucormycosis: A Descriptive Multisite Study from India. Issue 6 (November 2021) - Gupta, Ritesh; Kesavadev, Jothydev; Krishnan, Gopika; Agarwal, Sanjay; Saboo, Banshi; Shah, Meet; Mittal, Atul; Durani, Suhail; Luthra, Atul; Singhal, Anuj; Rasheed, Muhammed; Rao, G.V.S.; et al.
Abstract: Background and aims: Mucormycosis is an invasive fungal infection and carries a significant morbidity and mortality. A number of cases of mucormycosis have been reported in association with COVID-19. In this study, a consortium of clinicians from various parts of India studied clinical profile of COVID-19 associated mucormycosis (CAM) and this analysis is presented here. Methods: Investigators from multiple sites in India were involved in this study. Clinical details included the treatment and severity of COVID-19, associated morbidities, as well as the diagnosis, treatment and prognosis of mucormycosis. These data were collected using google spreadsheet at one centre. Descriptive analysis was done. Results: There were 115 patients with CAM. Importantly, all patients had received corticosteroids. Diabetes was present in 85.2% of patients and 13.9% of patients had newly detected diabetes. The most common site of involvement was rhino-orbital. Mortality occurred in 25 (21.7%) patients. On logistic regression analysis, CT scan-based score for severity of lung involvement was associated with mortality. Conclusion: Universal administration of corticosteroids in our patients is notable. A large majority of patients had diabetes, while mortality was seen in ∼1/5th of patients, lower as compared to recently published data. Highlights: All patients with COVID-19 associated mucormycosis (CAM, n 115) had received corticosteroids during treatment for COVID-19. Diabetes was present in 85.2% of patients with CAM. Pneumonia severity score on CT scan was associated with mortality due to CAM.